Reliefne značilnosti tal in objedanje mladja s strani velikih rastlinojedih parkljarjev v jelovo-bukovem gozdu - Roženbergar, Dušan (Acta silvae et ligni, 2019)
Ungulates affect the development of forest ecosystems in different ways. The most negative impact is a result of a long-term intense overbrowsing of regeneration. The aim of this study was to determine the effect of habitat characteristics and topography on browsing damage to regeneration in Dinaric beech-fir forests. The average damage rate across all tree species of regeneration was 70 %, and the analysis of the regeneration height structure showed that there was no recruitment of sycamore maple and silver fir into the upper height layers. We confirmed the influence of cover level for ungulates and topographical position on the browsing damage rate. Most of the damages were recorded on ridges and in sinkholes. According to the results of our study, it will not be possible to provide, at current browsing rates, admixtures of silver fir and sycamore maple in the upper canopy. In order to achieve diverse structure and species composition in these forests, in addition to silvicultural measures, it will be necessary to continue active management of ungulate populations focused on reducing densities.
Keywords: Abies alba; Acer pseudoplatanus; browsing; Fagus sylvatica; gojenje gozdov; objedanje; pomlajevanje; regeneration; relief; topography; ungulates, silviculture; veliki rastlinojedi parkljarji